Factors Influencing Malaysian Pineapple Smallholders Intention To Adopt MyGAP And MPIB Roles To Inspire The Growers To Obtain MyGAP Certification - Fam, Soo Fen; Laham, Jamaliah; Sapak, Zaiton; Zun, Liang Chuan; Ahamat, Amiruddin; Wan Zin, Wan Zawaiah; Suhartono, Suhartono (Gyandhara International Academic Publications, 2019)
Purpose of the study: The study aims to identify the factors influencing growers‟ intention to adopt MyGAP and MPIB roles and to inspire the pineapple growers to obtain MyGAP certificate. Methodology: Questionnaires were distributed to a sample of 52 pineapple smallholder respondents in the study area. Descriptive analysis and binary logistic regressions were conducted using IMB SPSS version 23. Main Findings and Novelty: The results of this study show that the three factors influencing pineapple smallholders‟ intention to adopt MyGAP are training, attitude and barriers. The odd ratios show growers who received training are four times more likely to adopt MyGAP. Applications of this study: MPIB has to conduct more training in order to inspire pineapple growers to obtain MyGAP certification. Meanwhile, the growers also have to change their attitude to accept MyGAP and overcome the perceived barriers for adopting MyGAP.